The UN declaration on the rights of peasants, national policies, and forestland rights of India's Adivasis. Issue 7 (9th August 2021) - Kashwan, Prakash; Kukreti, Ishan; Ranjan, Rahul
ABSTRACT: The United Nations Declaration on the Rights of Peasants and Other People Working in Rural Areas (UNDROP) is one of the most ambitious UN declarations. We analyse the policy and legal challenges of protecting these rights vis-à-vis India's indigenous Adivasi peasants. Longstanding social and political mobilizations have enabled Adivasis to secure significant statutory and legal rights, which address the goals of land rights and food sovereignty, sustainable development, and socially just climate action. However, powerful actors and agencies opposed to these rights hold considerable sway over India's political and judicial institutions. For example, contrary to its reputation as an activist court, India's Supreme Court has failed to protect Adivasi rights. Such countermobilization against Adivasi rights, especially by some environmental groups advocating for the enclosure of Adivasi lands for the sake of wildlife and biodiversity conservation, underscores the difficulty of enforcing economic and social rights. This article offers five key insights to inform future human rights advocacy and praxis to protect the rights enshrined within UNDROP. Our analysis identifies synergies between international human rights activism and the national and subnational struggles to protect peasant rights.